Muslim Identity Formation in Contemporary Societies - Yucel, Salih; Whyte, Shaheen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents a global and multidisciplinary approach towards the cultivation of Muslim identities in various socio-political, cultural and geographical contexts. It draws on empirical case studies conducted on Muslim communities in Britain, France, Pakistan, Turkey and Australia. The covered topics include: the identity of Deobandi ulama in contemporary Britain; Muslim loyalty and identity formation in France; the cultural identity of Jafari Shi'is in Turkey; religious attire among male Tablighi adherents in Pakistan; and the question of intra-Muslim dialogue among Australian Muslims. This reprint provides profound insights into how Muslims navigate socio-political pressures and Islamophobia to break stereotypes and assert their religiosity in diverse political settings. The contributions underscore and challenge important questions regarding Muslim loyalty to non-Muslim states, the treatment of Muslim minority groups by governments, the status of intra-Muslim relations, and non-discursive expressions of identity through religious attire.